Antecedent consumer factors, consequential branding outcomes and measures of online consumer engagement: current research and future directions. Issue 2 (4th June 2020) - Vander Shee, Brian A.; Peltier, James; Dahl, Andrew J.
Abstract : Purpose: The purpose of this study is to summarize the findings of consumer factor research and to suggest future lines of inquiry connected to branding outcomes. Consumers are comfortable with social media and accept firms occupying the same digital space. However, some consumers more readily engage with firms online than others. Consumer factor antecedents are numerous and yet not fully explored. Online consumer engagement has also been defined and measured in various ways. The resultant outcomes related to branding also have implications for future consumer engagement. Summarizing the findings of consumer factor research and suggesting future lines of inquiry connected to branding outcomes will enhance the understanding of consumer engagement and branding strategies to maximize marketing return on investment. Design/methodology/approach: The authors review literature examining key constructs and sub-dimensions on how consumer factors impact brand engagement and brand outcomes. Findings: Three major research areas specific to consumer factors were identified: consumer status, consumer disposition, personality trait, intrinsic motivation, extrinsic motivation and cultural dimensions. Brand engagement was explored relative to affective, cognitive and behavioral engagement. Lastly, six brand outcomes were explored: brand status, disposition, attitude, affirmation connection and aversion. Practical implications: This review contributes to the literature through a deeper understanding of consumer factors that lead to consumer engagement and the resultant branding factors of consumer engagement. The authors offer framework that both identifies future research needs, and insights into how firms may create, grow and enhance consumer–brand engagement. Originality/value: Given the dearth of comprehensive brand engagement frameworks in the literature, the authors offer insights into how consumer factors serve as antecedents to brand engagement and identify a research agenda for advancing the field.